直齿圆柱齿轮内部缺陷的超声自动检测 - 吕铎; 杨岳; 李雄兵; 刘希玲 (Jixie chuandong)
The internal flaws in gearswhich occur during manufacturing and service have great effect on operation safety of equipments.A scheme of automatic ultrasonic testing based on the XYmotion platformis presented,and the corresponding automatic ultrasonic testing system is designed and analyzed.According to the characteristic of the cylindrical spur gear profile,the probe path is planned on the principle of the longitudinal wave testing and zigzag shaped scan.The signal feature of the ultrasonic testing on gear is modeled and analyzed to extract the position of the internal flaws.Moreover,a software is developed to realize the signal acquisition,the motion control and the visualization of the internal flaws.The validty of the work is verified by an ultrasonic C-scan experiment on gear.